2015
DOI: 10.1111/rda.12553
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Limits Using Antimicrobial Peptides in Boar Semen Preservation

Abstract: Contents Antibiotics are of great importance for the preservation of ejaculates for livestock breading. The use of antibiotics, however, is not an appropriate compensation for a lack of hygiene standards in artificial insemination (AI) centres. Sophisticated hygiene management and the proper identification of hygienic critical control points (HCCPs) at AI centres provide the basis for counteracting the development of antibiotic resistance in contaminant bacteria and their settlement in AI centres. In recent ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 57 publications
1
11
0
3
Order By: Relevance
“…Antibiotics were added to semen extenders as a preventive measure to reduce bacterial contamination (5,6). Some level of drug resistance has been observed among isolates from boar semen against antibiotics commonly used as preservative antimicrobials in commercial porcine semen extenders (3,8 On the other hand, our results showed an important resistance to penicillin (>75%) and lincomycin (>87.5%). It has been shown that when utilizing β-lactams in a mixed bacterial population of susceptible and resistant cells, resistant cells quickly (in as little as 2.5 h) degrade the β-lactam, eliminating whatever selection pressure the antimicrobial provided (25).…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…Antibiotics were added to semen extenders as a preventive measure to reduce bacterial contamination (5,6). Some level of drug resistance has been observed among isolates from boar semen against antibiotics commonly used as preservative antimicrobials in commercial porcine semen extenders (3,8 On the other hand, our results showed an important resistance to penicillin (>75%) and lincomycin (>87.5%). It has been shown that when utilizing β-lactams in a mixed bacterial population of susceptible and resistant cells, resistant cells quickly (in as little as 2.5 h) degrade the β-lactam, eliminating whatever selection pressure the antimicrobial provided (25).…”
Section: Discussionmentioning
confidence: 46%
“…Water was the major source of contamination. Additionally, our results on evaluation of susceptibility to antimicrobial agents has shown a good efficacy (in vitro) of aminoglycosides (neomycin and gentamicin) on de semen porcino comercial (3,8 Por otro lado, nuestros resultados mostraron una importante resistencia a la penicilina (>75%) y a la lincomicina (>87.5%). Se ha demostrado que al utilizar β-lactams en una población bacteriana mixta de células susceptibles y resistentes, las células resistentes degradan rápidamente (en tan sólo 2,5 h) el β-lactam, eliminando cualquier presión de selección que proporcione el antimicrobiano (25).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Their presence in the cells and tissues of the uterus, fetus and the neonate indicates an important role in immunity during pregnancy and in early life [625; 632-636]. Unsurprisingly, they have been proposed as agents for use in preventing the transmission of STDs [637; 638], and as antimicrobials for addition to stored semen for use in agriculture [639][640][641][642][643]. Our interest here, however, is around whether there are natural AMPs in human (or animal) semen, and the answer is in the affirmative.…”
Section: Antimicrobial Components Of Human Semen a Part Of Resistancmentioning
confidence: 99%